What Pd Can't Teach; What It Can - Hudelson, Joshua (Revista Vórtex, 2021)
Pure Data's long appeal is partly owed to its visual layout and intuitive mode of use. This might lead one to consider it a useful pedagogical tool, even if it now meets stiff competition from glitzier and more user-friendly applications. In the author's experience, however, Pd's ambiguous location on the spectrum of virtualization makes it bad for teaching but gives it a far more important function for composers. In occupying an uncanny valley between the digital-as-digital and the digital-as-analog, it resists the general tendency of digital technology to obscure awareness of itself, that is, of the digital computer as the current high watermark of a longer history of rationalization. It thus pushes composers of computer music back towards the questions that are at the heart of their work. This dynamic is illustrated by the author's experience of developing and tinkering with a novel technique of sound synthesis.